Magnesium hydroxide flame retardant suitable for high-speed extrusion cable and preparation method thereof
By introducing additives such as polypropylene carbonate, tetrabutyl ammonium bromide and sodium stearate in the preparation process of magnesium hydroxide flame retardant, the problem of poor adaptability of traditional magnesium hydroxide flame retardant in high-speed extrusion cable processing is solved, and the good dispersion and processing performance of the flame retardant is achieved, and the production efficiency and flame retardant performance of the cable are improved.
Patent Information
- Application Number
- CN202510369730.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
Traditional magnesium hydroxide flame retardants have poor adaptability in high-speed extrusion cable processing, resulting in poor dispersion, reduced processing fluidity and insufficient interface bonding, which seriously restricts production efficiency.
By introducing functional additives such as polypropylene carbonate, tetrabutyl ammonium bromide and sodium stearate, a magnesium hydroxide flame retardant with a particle size of 1.0-1.3 μm was prepared. Multi-step processes include stirring, vacuum filtration of the filter membrane, dry ball milling and airflow crushing to optimize the dispersion and processing performance of the flame retardant.
The dispersion, processing performance and flame retardant efficiency of the flame retardant are significantly improved, the interface bonding strength with the polypropylene matrix is improved, and the processing stability and surface quality of the cable are improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardants, and in particular to a magnesium hydroxide flame retardant suitable for high-speed extrusion cables and a preparation method thereof. Background Art
[0002] As an environmentally friendly inorganic flame retardant, magnesium hydroxide has become an important choice to replace traditional halogen flame retardants because it releases crystal water (absorbs about 1.44 kJ / g of heat) during thermal decomposition at 300-340℃, generates a magnesium oxide layer with barrier effect, and the decomposition product is non-toxic and harmless. Its flame retardant mechanism includes three effects: heat absorption and cooling, gas phase dilution and solid phase barrier. This synergistic effect makes it show unique advantages in polymer materials in the fields of wires and cables, electronic appliances, etc.
[0003] However, the strong polarity and high surface energy of magnesium hydroxide (about 200-300 mJ / m²) lead to poor interfacial compatibility in non-polar polymer matrices such as polyethylene and polypropylene, and it is easy to form micron-sized agglomerates (usually with a particle size of >5μm). This phase separation phenomenon not only causes a decrease in the volume filling effect of the flame retardant (the critical addition amount needs to reach 60-65wt%), but also triggers stress concentration points, reducing the tensile strength of the material by 40%-50% and the impact strength by more than 60%. During high-speed extrusion processing (screw speed >500 rpm), the shear friction between the agglomerated particles and the twin screws will cause local overheating (temperature fluctuations of up to ±15°C), resulting in a 30%-50% decrease in the melt flow index (MFI), which seriously restricts production efficiency.
[0004] Although surface modification can improve dispersibility by coating with stearic acid or silane coupling agent, conventional dry modification has problems such as low coating rate and poor thermal stability. Although wet modification can improve coating uniformity, it faces industrial bottlenecks such as complex process (requires solvent recovery) and increased costs. Although nano magnesium hydroxide studied in recent years can improve dispersibility, the surge in specific surface area will intensify the van der Waals force between particles, making it easier to form secondary agglomerations in high-speed shear fields.
[0005] Therefore, the development of magnesium hydroxide flame retardants with good dispersibility, processing fluidity and interface bonding strength has become the key to breaking through the bottleneck of technological upgrading in the cable industry. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide a magnesium hydroxide flame retardant suitable for high-speed extrusion cables and a preparation method thereof, so as to solve the problem of poor adaptability of traditional magnesium hydroxide flame retardants in high-speed extrusion cable processing.
[0007] Based on the above purpose, the present invention provides a method for preparing magnesium hydroxide flame retardant suitable for high-speed extrusion cables, which is prepared by the following steps: (1) Add magnesium sulfate heptahydrate, polypropylene carbonate, and tetrabutylammonium bromide into deionized water, heat to 55-65°C, stir at 500-700 rpm for 25-35 min, then heat to 80-90°C, add sodium hydroxide aqueous solution for the first time, stir and react for 2-4 h, add sodium stearate, add sodium hydroxide aqueous solution for the second time, and continue stirring for 2-4 h to obtain a magnesium hydroxide precursor suspension; (2) transferring the magnesium hydroxide precursor suspension to a Buchner funnel, vacuum filtering with a polytetrafluoroethylene filter membrane, washing, and obtaining a filter cake; (3) The filter cake is vacuum dried, then added to a ball mill, dry-milled at 300-500 rpm for 40-50 min, and passed through a 300-350 mesh vibrating sieve to obtain primary powder; (4) The primary powder is crushed by a jet mill to obtain a magnesium hydroxide flame retardant having a particle size D50 of 1.0-1.3 μm suitable for high-speed extrusion cables.
[0008] Preferably, in step (1), the dosage ratio of magnesium sulfate heptahydrate, polypropylene carbonate, tetrabutylammonium bromide, deionized water, sodium hydroxide aqueous solution and sodium stearate is 20-30 g: 3-4 g: 0.01-0.03 g: 80-120 mL: 63-77 mL: 0.5-1 g.
[0009] Preferably, the concentration of the sodium hydroxide aqueous solution in step (1) is 2.8-3.2 mol / L.
[0010] Preferably, in step (1), the volume ratio of the first dropwise addition of the sodium hydroxide aqueous solution to the second dropwise addition of the sodium hydroxide aqueous solution is 45-55:18-22.
[0011] Preferably, the weight average molecular weight of the polypropylene carbonate in step (1) is 6000-10000.
[0012] Preferably, the pore size of the polytetrafluoroethylene filter membrane in step (2) is 0.4-0.5 μm.
[0013] Preferably, the vacuum drying temperature in step (3) is 80-90° C., and the vacuum degree is -0.08±0.01 MPa.
[0014] Preferably, in the step (3), zirconia balls are used as the ball milling medium, and the ball-to-material ratio is 5:1.
[0015] Preferably, the mesh size of the vibrating screen in step (3) is 300-350 meshes.
[0016] Furthermore, the present invention also provides a magnesium hydroxide flame retardant suitable for high-speed extrusion cables, which is obtained by the preparation method of the magnesium hydroxide flame retardant suitable for high-speed extrusion cables.
[0017] Beneficial effects of the present invention: The invention provides a method for preparing a magnesium hydroxide flame retardant. Functional additives such as polypropylene carbonate, tetrabutylammonium bromide and sodium stearate are introduced during the preparation process, thereby significantly improving the dispersibility, processing performance and flame retardant efficiency of the flame retardant.
[0018] The polypropylene carbonate introduced in the present invention undergoes controllable hydrolysis in an alkaline environment, and the generated active groups form chemical bonds with the crystal faces of magnesium hydroxide, thereby inhibiting excessive particle growth and optimizing the surface chemical properties of the particles, thereby improving the dispersion uniformity of the flame retardant in the polypropylene matrix.
[0019] The tetrabutylammonium bromide introduced in the present invention induces magnesium hydroxide to form high-diameter-to-thickness ratio flaky particles through dynamic coordination and surface adsorption mechanisms, thereby improving the particle morphology and reducing processing shear resistance, while enhancing the interface bonding strength between the flame retardant and the polypropylene matrix.
[0020] The sodium stearate introduced in the present invention reduces the surface energy of the particles through surface modification, and provides a lubricating effect during high-speed extrusion, effectively reducing mold wear and melt temperature fluctuations, and improving processing stability and cable surface quality.
[0021] The present invention realizes efficient preparation of flame retardants through multi-scale regulation, is suitable for high-speed extrusion processes, and has important industrial application value. DETAILED DESCRIPTION
[0022] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0023] Example 1
[0024] (1) Add 20 g of magnesium sulfate heptahydrate, 3 g of polypropylene carbonate (Mw=6000), and 0.01 g of tetrabutylammonium bromide to 80 mL of deionized water, heat to 55 °C, stir at 500 rpm for 25 min, then heat to 80 °C, drop 45 mL of 2.8 mol / L sodium hydroxide aqueous solution, stir for 2 h, add 0.5 g of sodium stearate, and then drop 18 mL of 2.8 mol / L sodium hydroxide aqueous solution, continue stirring for 2 h, and obtain a magnesium hydroxide precursor suspension; (2) transferring the magnesium hydroxide precursor suspension to a Buchner funnel, vacuum filtering with a 0.4 μm polytetrafluoroethylene filter membrane, and washing alternately with deionized water and anhydrous ethanol three times to obtain a filter cake; (3) The filter cake was placed in a vacuum drying oven and dried at 80°C and -0.07 MPa for 16 h. The dried product was added to a planetary ball mill with zirconium oxide balls as the ball milling medium (ball-to-material ratio 5:1). The product was dry-milled at 300 rpm for 40 min and passed through a 300-mesh vibrating sieve to obtain primary powder. (4) The primary powder is crushed by a jet mill to obtain a magnesium hydroxide flame retardant with a particle size D50 of 1.0 μm suitable for high-speed extrusion of cables.
[0025] Example 2
[0026] (1) Add 24.5 g of magnesium sulfate heptahydrate, 3.5 g of polypropylene carbonate (Mw=8000), and 0.02 g of tetrabutylammonium bromide to 100 mL of deionized water, heat to 60 °C, stir at 600 rpm for 30 min, then heat to 85 °C, drop 50 mL of 3.0 mol / L sodium hydroxide aqueous solution, stir for 3 h, add 0.7 g of sodium stearate, and then drop 20 mL of 3.0 mol / L sodium hydroxide aqueous solution, continue stirring for 3 h to obtain a magnesium hydroxide precursor suspension; (2) transferring the magnesium hydroxide precursor suspension to a Buchner funnel, vacuum filtering with a 0.45 μm polytetrafluoroethylene filter membrane, and washing alternately with deionized water and anhydrous ethanol three times to obtain a filter cake; (3) The filter cake was placed in a vacuum drying oven and dried at 85°C and -0.08 MPa for 18 h. The dried product was added to a planetary ball mill with zirconium oxide balls as the ball milling medium (ball-to-material ratio 5:1). The product was dry-milled at 400 rpm for 45 min and passed through a 325-mesh vibrating sieve to obtain primary powder. (4) The primary powder is crushed by a jet mill to obtain a magnesium hydroxide flame retardant with a particle size D50 of 1.2 μm suitable for high-speed extrusion of cables.
[0027] Example 3
[0028] (1) Add 30 g of magnesium sulfate heptahydrate, 4 g of polypropylene carbonate (Mw=10000), and 0.03 g of tetrabutylammonium bromide to 120 mL of deionized water, heat to 65 °C, stir at 700 rpm for 35 min, then heat to 90 °C, drop 55 mL of 3.2 mol / L sodium hydroxide aqueous solution, stir for 4 h, add 1 g of sodium stearate, and then drop 22 mL of 3.2 mol / L sodium hydroxide aqueous solution, continue stirring for 4 h to obtain a magnesium hydroxide precursor suspension; (2) transferring the magnesium hydroxide precursor suspension to a Buchner funnel, vacuum filtering with a 0.5 μm polytetrafluoroethylene filter membrane, and washing alternately with deionized water and anhydrous ethanol three times to obtain a filter cake; (3) The filter cake was placed in a vacuum drying oven and dried at 90°C and -0.09 MPa for 20 h. The dried product was added to a planetary ball mill with zirconium oxide balls as the ball milling medium (ball-to-material ratio 5:1). The product was dry-milled at 500 rpm for 50 min and passed through a 350-mesh vibrating sieve to obtain primary powder. (4) The primary powder is crushed by a jet mill to obtain a magnesium hydroxide flame retardant with a particle size D50 of 1.3 μm suitable for high-speed extrusion cables.
[0029] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that: polypropylene carbonate is not added in step (1); The specific steps are as follows: (1) Add 24.5 g of magnesium sulfate heptahydrate and 0.02 g of tetrabutylammonium bromide to 100 mL of deionized water, heat to 60 ° C, stir at 600 rpm for 30 min, then heat to 85 ° C, drop 50 mL of 3.0 mol / L sodium hydroxide aqueous solution, stir for 3 h, add 0.7 g of sodium stearate, and then drop 20 mL of 3.0 mol / L sodium hydroxide aqueous solution, continue stirring for 3 h to obtain a magnesium hydroxide precursor suspension; (2) transferring the magnesium hydroxide precursor suspension to a Buchner funnel, vacuum filtering with a 0.45 μm polytetrafluoroethylene filter membrane, and washing alternately with deionized water and anhydrous ethanol three times to obtain a filter cake; (3) The filter cake was placed in a vacuum drying oven and dried at 85°C and -0.08 MPa for 18 h. The dried product was added to a planetary ball mill with zirconium oxide balls as the ball milling medium (ball-to-material ratio 5:1). The product was dry-milled at 400 rpm for 45 min and passed through a 325-mesh vibrating sieve to obtain primary powder. (4) The primary powder is crushed by a jet mill to obtain a magnesium hydroxide flame retardant with a particle size D50 of 1.2 μm suitable for high-speed extrusion of cables.
[0030] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that: tetrabutylammonium bromide is not added in step (1); The specific steps are as follows: (1) Add 24.5 g of magnesium sulfate heptahydrate and 3.5 g of polypropylene carbonate (Mw=8000) into 100 mL of deionized water, heat to 60 °C, stir at 600 rpm for 30 min, then heat to 85 °C, drop 50 mL of 3.0 mol / L sodium hydroxide aqueous solution, stir for 3 h, add 0.7 g of sodium stearate, then drop 20 mL of 3.0 mol / L sodium hydroxide aqueous solution, continue stirring for 3 h, and obtain a magnesium hydroxide precursor suspension; (2) transferring the magnesium hydroxide precursor suspension to a Buchner funnel, vacuum filtering with a 0.45 μm polytetrafluoroethylene filter membrane, and washing alternately with deionized water and anhydrous ethanol three times to obtain a filter cake; (3) The filter cake was placed in a vacuum drying oven and dried at 85°C and -0.08 MPa for 18 h. The dried product was added to a planetary ball mill with zirconium oxide balls as the ball milling medium (ball-to-material ratio 5:1). The product was dry-milled at 400 rpm for 45 min and passed through a 325-mesh vibrating sieve to obtain primary powder. (4) The primary powder is crushed by a jet mill to obtain a magnesium hydroxide flame retardant with a particle size D50 of 1.2 μm suitable for high-speed extrusion of cables.
[0031] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that sodium stearate is not added in step (1): The specific steps are as follows: (1) Add 24.5 g of magnesium sulfate heptahydrate, 3.5 g of polypropylene carbonate (Mw=8000), and 0.02 g of tetrabutylammonium bromide to 100 mL of deionized water, heat to 60 °C, stir at 600 rpm for 30 min, then heat to 85 °C, drop 50 mL of 3.0 mol / L sodium hydroxide aqueous solution, stir for 3 h, then drop 20 mL of 3.0 mol / L sodium hydroxide aqueous solution, continue stirring for 3 h, and obtain a magnesium hydroxide precursor suspension; (2) transferring the magnesium hydroxide precursor suspension to a Buchner funnel, vacuum filtering with a 0.45 μm polytetrafluoroethylene filter membrane, and washing alternately with deionized water and anhydrous ethanol three times to obtain a filter cake; (3) The filter cake was placed in a vacuum drying oven and dried at 85°C and -0.08 MPa for 18 h. The dried product was added to a planetary ball mill with zirconium oxide balls as the ball milling medium (ball-to-material ratio 5:1). The product was dry-milled at 400 rpm for 45 min and passed through a 325-mesh vibrating sieve to obtain primary powder. (4) The primary powder is crushed by a jet mill to obtain a magnesium hydroxide flame retardant with a particle size D50 of 1.2 μm suitable for high-speed extrusion of cables.
[0032] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that: in step (1), 50 mL of a 3.0 mol / L sodium hydroxide aqueous solution is first added dropwise, stirred for reaction for 3 h, then 20 mL of a 3.0 mol / L sodium hydroxide aqueous solution is added dropwise, stirred for reaction for 3 h, and then sodium stearate is added and stirred for 20 min to obtain a magnesium hydroxide precursor suspension; The specific steps are as follows: (1) Add 24.5 g of magnesium sulfate heptahydrate, 3.5 g of polypropylene carbonate (Mw=8000), and 0.02 g of tetrabutylammonium bromide to 100 mL of deionized water, heat to 60 °C, stir at 600 rpm for 30 min, then heat to 85 °C, first drop 50 mL of 3.0 mol / L sodium hydroxide aqueous solution, stir for 3 h, then drop 20 mL of 3.0 mol / L sodium hydroxide aqueous solution, stir for 3 h, then add sodium stearate, stir for 20 min, and obtain a magnesium hydroxide precursor suspension; (2) transferring the magnesium hydroxide precursor suspension to a Buchner funnel, vacuum filtering with a 0.45 μm polytetrafluoroethylene filter membrane, and washing alternately with deionized water and anhydrous ethanol three times to obtain a filter cake; (3) The filter cake was placed in a vacuum drying oven and dried at 85°C and -0.08 MPa for 18 h. The dried product was added to a planetary ball mill with zirconium oxide balls as the ball milling medium (ball-to-material ratio 5:1). The product was dry-milled at 400 rpm for 45 min and passed through a 325-mesh vibrating sieve to obtain primary powder. (4) The primary powder is crushed by a jet mill to obtain a magnesium hydroxide flame retardant with a particle size D50 of 1.2 μm suitable for high-speed extrusion of cables.
[0033] Performance Test: Melt flow rate: The flame retardant and polypropylene (melt index of 20 g / 10 min at 190°C and 2.16 kg) were blended and granulated at 190°C in a mass ratio of 30:100. The melt flow index was measured using a melt flow rate meter at 230°C and 2.16 kg load. The results are shown in Table 1.
[0034] Oxygen index determination: According to GB / T 2406.2-2023 test, the flame retardant and polypropylene (melt index of 20g / 10min at 190℃ and 2.16kg) were blended and granulated at a mass ratio of 15:100 at 190℃, and the copper conductor was extruded and coated at a line speed of 500m / min to prepare a cable with a coating thickness of 0.7mm; it was vertically installed in the combustion tube of the oxygen index meter, the initial oxygen concentration was set to 28%, and the top ignition method was used to record the minimum oxygen concentration required for continuous burning of 30mm in length. The results are shown in Table 1.
[0035] Vertical burning test: According to GB / T 2408-2021, the flame retardant and polypropylene (melt index of 20g / 10min at 190℃ and 2.16kg) are blended and granulated at a mass ratio of 15:100 at 190℃, and the copper conductor is extruded and coated at a line speed of 500m / min to prepare a cable with a coating thickness of 0.7mm; it is fixed vertically in the combustion box and a 20mm blue flame is applied for 10 seconds; the afterburning time after the flame is removed for the first time and whether the dripping material ignites the absorbent cotton are recorded, and the ignition is repeated until V-0, V-1 or V-2 classification is obtained. The results are shown in Table 1.
[0036] Extruded cable surface quality inspection: According to GB / T 2951.11-2008 test, the flame retardant and polypropylene (190°C, melt index of 20g / 10min at 2.16kg) were blended and granulated at 190°C in a mass ratio of 15:100, and the copper conductor was extruded and coated at a line speed of 500m / min to prepare a cable with a coating thickness of 0.7mm; the surface roughness Ra value within a length of 10 cm was measured using a three-dimensional surface profiler, and the results are shown in Table 1.
[0037] Table 1 Performance test results Melt flow rate / g / 10min Oxygen index / % Vertical burning level Surface roughness Ra / μm Example 1 18.1 32.8 V-0 1.4 Example 2 18.5 33.5 V-0 1.2 Example 3 18.3 33.9 V-0 1.3 Comparative Example 1 16.5 27.4 V-1 2.8 Comparative Example 2 17.4 29.5 V-1 2.2 Comparative Example 3 16.3 31.8 V-0 3.0 Comparative Example 4 17.8 31.2 V-0 2.1 Data Analysis: From the data of Examples 1-3 in Table 1, it can be seen that the magnesium hydroxide flame retardant suitable for high-speed extrusion cable prepared by the present invention has excellent processing performance and flame retardant performance, and the performance of the melt flow rate shows that the flame retardant is fully compatible with the polypropylene matrix and maintains good fluidity and processing stability during high-speed extrusion. The lower surface roughness reflects that the magnesium hydroxide flame retardant has a lubricating effect during high-speed extrusion, reducing the mechanical wear between the mold and the mold. This may be because the modification of sodium stearate and polypropylene carbonate reduces the roughness of the particles and improves the compatibility with the matrix, thereby optimizing the processing surface quality of the cable.
[0038] It can be seen from the data of Example 2 and Comparative Example 1 in Table 1 that the introduction of polypropylene carbonate significantly optimizes the performance of the flame retardant. The polymer may undergo controllable hydrolysis in an alkaline reaction environment, and the generated active groups are chemically bonded to the crystal faces of magnesium hydroxide, thereby forming a steric hindrance layer on the particle surface. This coating effect not only inhibits the excessive growth of particles, but also improves the dispersion uniformity of the flame retardant in the polypropylene melt. In addition, the decomposition products of polypropylene carbonate may participate in the carbonization reaction during the combustion process, and cooperate with the water vapor released by magnesium hydroxide to form a multi-level barrier structure, effectively delaying the diffusion of pyrolysis products. Surface chemical modification also reduces the interfacial tension between the particles and the polymer segments, so that the flame retardant can still maintain stable flow characteristics under high shear extrusion conditions, which is crucial to maintaining the dimensional accuracy of the cable coating.
[0039] As can be seen from the data of Example 2 and Comparative Example 2 in Table 1, tetrabutylammonium bromide significantly optimizes the flame retardant performance through a synergistic catalytic mechanism: as a phase transfer catalyst, its quaternary ammonium cation forms a dynamic coordination with the carbonate group of polypropylene carbonate, reduces the activation energy of alkaline hydrolysis, and promotes the directional fracture of the polymer to generate terminal carbonate groups. These active groups are combined with the hydroxyl groups of the magnesium hydroxide crystal surface through hydrogen bonds and ionic bonds to construct a stable organic-inorganic hybrid interface layer, which effectively inhibits particle agglomeration. In the crystal growth stage, tetrabutylammonium bromide selectively adsorbs on the specific crystal surface of magnesium hydroxide, and induces the formation of lamellar primary particles with a high diameter-to-thickness ratio by regulating the surface energy distribution. This morphological feature makes it easier to obtain micron-sized particles with smooth edges in subsequent ball milling, reducing processing shear resistance. The oligomer fragments produced by hydrolysis migrate to the polypropylene-flame retardant interface during melt blending, and their polar ends are anchored on the flame retardant surface, and the non-polar segments are entangled with the polypropylene matrix to form a gradient transition interface structure, which alleviates the stress concentration caused by the difference in the modulus of the two phases. This multi-scale regulation achieves a synergistic improvement in flame retardant dispersibility, processing rheology and flame retardant efficiency.
[0040] As can be seen from the data of Example 2 and Comparative Example 3 in Table 1, the surface modification of sodium stearate significantly improves the processing adaptability of the flame retardant. Its long-chain alkyl forms a directional hydrophobic layer on the surface of magnesium hydroxide particles through chemical adsorption. This organic-inorganic hybrid structure not only reduces the surface energy of the particles, but also inhibits the van der Waals force between the particles through the steric hindrance effect. During high-speed extrusion, this surface lubrication layer reduces the friction heat accumulation between the flame retardant and the screw and the metal surface of the mold cavity, thereby maintaining the stability of the melt temperature. In addition, the decomposition temperature of sodium stearate matches the polypropylene processing window, and it partially migrates to the matrix-flame retardant interface during the melt mixing stage, acting as a compatibilizer, further strengthening the bonding strength of the two-phase interface.
[0041] From the data of Example 2 and Comparative Example 4 in Table 1, it can be seen that the introduction of sodium stearate in the crystal growth stage can effectively improve the processing adaptability of the flame retardant. This is because the introduction of sodium stearate in the late stage of crystal growth can regulate the surface energy distribution of particles by selective adsorption on specific crystal planes, so that the sphericity of particles after airflow crushing is significantly improved, and the optimization of process timing realizes the coordinated control of crystal morphology-surface characteristics-crushing efficiency, which is the core technical feature of obtaining high-performance flame retardants.
[0042] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A method for preparing a magnesium hydroxide flame retardant suitable for high-speed extrusion cables, characterized in that: Prepared by the following steps: (1) Add magnesium sulfate heptahydrate, polypropylene carbonate, and tetrabutylammonium bromide into deionized water, heat to 55-65°C, stir at 500-700 rpm for 25-35 min, then heat to 80-90°C, add sodium hydroxide aqueous solution for the first time, stir and react for 2-4 h, add sodium stearate, add sodium hydroxide aqueous solution for the second time, and continue stirring for 2-4 h to obtain a magnesium hydroxide precursor suspension; (2) transferring the magnesium hydroxide precursor suspension to a Buchner funnel, vacuum filtering with a polytetrafluoroethylene filter membrane, washing, and obtaining a filter cake; (3) The filter cake is vacuum dried, then added to a ball mill, dry-milled at 300-500 rpm for 40-50 min, and passed through a 300-350 mesh vibrating sieve to obtain primary powder; (4) crushing the primary powder by a jet mill to obtain a magnesium hydroxide flame retardant having a particle size D50 of 1.0-1.3 μm suitable for high-speed extrusion cables; In the step (1), the ratio of magnesium sulfate heptahydrate, polypropylene carbonate, tetrabutylammonium bromide, deionized water, sodium hydroxide aqueous solution and sodium stearate is 20-30 g: 3-4 g: 0.01-0.03 g: 80-120 mL: 63-77 mL: 0.5-1 g; The concentration of the sodium hydroxide aqueous solution in step (1) is 2.8-3.2 mol / L; In the step (1), the volume ratio of the first drop of the sodium hydroxide aqueous solution to the second drop of the sodium hydroxide aqueous solution is 45-55:18-22.
2. The method for preparing a magnesium hydroxide flame retardant suitable for high-speed extrusion cable according to claim 1, characterized in that: The weight average molecular weight of the polypropylene carbonate in step (1) is 6000-10000.
3. The method for preparing a magnesium hydroxide flame retardant suitable for high-speed extrusion cable according to claim 1, characterized in that: The pore size of the polytetrafluoroethylene filter membrane in step (2) is 0.4-0.5 μm.
4. The method for preparing a magnesium hydroxide flame retardant suitable for high-speed extrusion cable according to claim 1, characterized in that: The temperature of vacuum drying in step (3) is 80-90° C., and the vacuum degree is -0.08±0.01 MPa.
5. The method for preparing a magnesium hydroxide flame retardant suitable for high-speed extrusion cable according to claim 1, characterized in that: In the step (3), zirconia balls are used as the ball milling medium, and the ball-to-material ratio is 5:
1.
6. The method for preparing a magnesium hydroxide flame retardant suitable for high-speed extrusion cable according to claim 1, characterized in that: The mesh size of the vibrating screen in step (3) is 300-350 meshes.
7. A magnesium hydroxide flame retardant suitable for high-speed extrusion cables, characterized in that: The magnesium hydroxide flame retardant suitable for high-speed extrusion cables is obtained by the preparation method of any one of claims 1 to 6.
Citation Information
Patent Citations
Method for preparing magnesium hydroxide fire retardant with lithium carbonate by-product magnesium oxide slag
CN102408121A
Method for preparing magnesium hydrate fire retardant through surface modification treatment by using composite wet method
CN103819935A
Method for preparing magnesium hydrate flame retardant
CN104592789A
Environment-friendly anti-flaming PVC solid pipe and preparation method thereof
CN109181137A
Method for preparing flame retardant by utilizing modifying technology and compounding technology
CN109233221A
Cited By
Preparation method of flaky magnesium hydroxide flame retardant
CN122011806A